Design and synthesis of tailored human caseinolytic protease P inhibitors. Issue 70 (15th August 2018) - Gronauer, Thomas F.; Mandl, Melanie M.; Lakemeyer, Markus; Hackl, Mathias W.; Meßner, Martina; Korotkov, Vadim S.; Pachmayr, Johanna; Sieber, Stephan A.
Abstract : To expedite functional studies of human ClpP we introduce tailored small molecule inhibitors. These compounds are active against the proteolytic ClpXP complex. Target identification elucidates anti-proliferative effects against cancer cells. Abstract : Human caseinolytic protease P (hClpP) is important for degradation of misfolded proteins in the mitochondrial unfolded protein response. We here introduce tailored hClpP inhibitors that utilize a steric discrimination in their core naphthofuran scaffold to selectively address the human enzyme. This novel inhibitor generation exhibited superior activity compared to previously introduced beta-lactones, optimized for bacterial ClpP. Further insights into the bioactivity and binding to cellular targets were obtained via chemical proteomics as well as proliferation- and migration studies in cancer cells.